NON-CALENDAR AND CALENDAR ATHROPONYMS IN RUSSIAN BUSINESS MONUMENTS ON RUSSIA AND INDIA RELATIONS IN THE 17TH CENTURY - Khabiba Gambarova (Web of Journals Publishing, 2025)
The article is devoted to studying the composition and characteristics of anthroponyms (non-calendar and calendar) recorded in the texts of Russian business monuments on relations between Russia and India in the XVII century. It is shown that the Christening of Russia led to the spread of not only baptismal but secular nicknames as well. Non-calendar personal names mainly reflect the order, time of birth, appearance of the child, and the parents’ attitude to the appearance of a new family member. The use of non-calendar anthroponyms in the texts of the Russian business writing under consideration in small quantities indicates the victory of the church name-bearer, who attracted the attention of the peasant population throughout Russia and received active support in the upper social strata. Non-calendar and calendar anthroponyms in the texts of business documents reflecting diplomatic relations between Russia and India in the 17th century indicate that the transition to the modern model of naming a person in the Russian language began precisely during this period. A widespread model for the formation of a Russian surname has become the addition of the suffixes -ов/-евor - инto the base - the name or nickname of the father. They were the formative elements of surnames in Russian lands. In the 17th century, a unified model for naming a person had not yet emerged. For this period, four-component, three-component and two-component person names were characteristic.
Keywords: Anthroponym; first name; surname; suffix; Russian non-calendar anthroponyms; Russian calendar anthroponyms; secular nickname; Russian business monuments.